2005
DOI: 10.1111/j.1365-2958.2005.04961.x
|View full text |Cite
|
Sign up to set email alerts
|

Genome scale analysis of diffusible signal factor regulon in Xanthomonas campestris pv. campestris: identification of novel cell–cell communication‐dependent genes and functions

Abstract: SummaryThe bacterial pathogen Xanthomonas campestris pv. campestris ( Xcc ) recruits a diffusible signal factor (DSF), which has recently been structurally characterized as cis -11-methyl-2-dodecenoic acid, as a cellcell communication signal to synchronize virulence gene expression and biofilm dispersal. In this study, we showed that despite the existance of phenotype variations in different Xcc isolates, the DSF-mediated functions were in general conserved. To investigate the genomic profiles of DSF regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
203
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 166 publications
(213 citation statements)
references
References 40 publications
6
203
0
4
Order By: Relevance
“…It is interesting in this context that DSF signaling has been shown to activate transcription of the gene encoding the cyclic-AMP receptor-like protein Clp (22), although the mechanism remains obscure. In Xcc, Clp regulates many functions, including the expression of genes encoding extracellular enzymes, but apparently is not involved in the regulation of biofilm dynamics (22,23). Intriguingly, recent findings have indicated that the promoter-binding activity of Clp is influenced negatively by cyclic di-GMP (24).…”
Section: Protein-protein Interactions and The Regulation Of Specific mentioning
confidence: 99%
“…It is interesting in this context that DSF signaling has been shown to activate transcription of the gene encoding the cyclic-AMP receptor-like protein Clp (22), although the mechanism remains obscure. In Xcc, Clp regulates many functions, including the expression of genes encoding extracellular enzymes, but apparently is not involved in the regulation of biofilm dynamics (22,23). Intriguingly, recent findings have indicated that the promoter-binding activity of Clp is influenced negatively by cyclic di-GMP (24).…”
Section: Protein-protein Interactions and The Regulation Of Specific mentioning
confidence: 99%
“…So far, only two extracellular enzyme genes (engA and prt1) have been demonstrated to be affected by a rpfA mutation (Wilson et al, 1998). Although details of regulatory circuits remain to be elucidated, recent microarray analyses have identified 165 Xcc genes that are regulated by RpfF/DSF (He et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These extracellular products have long been considered important virulence determinants (Chan & Goodwin, 1999;Chang et al, 2001;Chou et al, 1997;Dow et al, 1987;Dums et al, 1991;Soby & Daniels, 1996;Yang & Tseng, 1988). Production of these determinants is regulated by the global transcription factor Clp (cAMP receptor protein-like protein) and the rpf (regulator of pathogenicity factors) gene cluster (Barber et al, 1997;de Crecy-Lagard et al, 1990;Dow et al, 2000;He et al, 2006He et al, , 2007Tang et al, 1991;Tseng et al, 1999;Wilson et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…As the cell surface is greatly deformed, the mopB mutation may have drastically changed the topology of GumB; without proper positioning of this important protein, the xanthan export machinery will malfunction. It is known that xanthan production is upregulated by DSF and Clp (He et al, 2006(He et al, , 2007Slater et al, 2000), but little is known about the roles of other possible regulators. In E. coli K1, expression of type 1 fimbriae, controlled by phase variation, is decreased upon deletion of ompA (Teng et al, 2006).…”
Section: Discussionmentioning
confidence: 99%